Piezoelectricity in two-dimensional materials - Wu, Tom (2015)
Powering up 2D materials: Recent experimental studies confirmed the existence of piezoelectricity—the conversion of mechanical stress into electricity—in two-dimensional single-layer MoS2 nanosheets. The results represent a milestone towards embedding low-dimensional materials into future disruptive technologies.